Alumina-Promoted Copper-Catalyzed Hydroboration of Alkynes - Barashkova, Xenia A.; Parulava, Mikhail J.; Kotovshchikov, Yury N.; Latyshev, Gennadij V.; Lukashev, Nikolay V.; Beletskaya, Irina P. (Synthesis, 2024)
Alumina was found to activate Cu(I) catalysts in hydroboration of alkynes. This allowed to develop a simple and efficient protocol for hydroboration of alkynes with B2Pin2 using inexpensive CuCl/PPh3 catalytic system. The approach does not require moisture-sensitive activators and stepwise preparation of ‘activated’ Cu complex. The developed conditions were applied to the preparation of β-styrylboronates from terminal and internal alkynes with excellent regio- and stereoselectivity. The procedure can also be extended to other terminal alkynes by the appropriate choice of ligand.
Keywords: alumina; copper; hydroboration; alkynes; vinylboronic esters; stereoselective synthesis